Mirror-mark tests performed on jackdaws reveal potential methodological problems in the use of stickers in avian mark-test studies. - Manuel Soler (Public Library of Science (PLoS), 2014)
Some animals are capable of recognizing themselves in a mirror, which is considered to be demonstrated by passing the mark test. Mirror self-recognition capacity has been found in just a few mammals having very large brains and only in one bird, the magpie (Pica pica). The results obtained in magpies have enormous biological and cognitive implications because the fact that magpies were able to pass the mark test meant that this species is at the same cognitive level with great apes, that mirror self-recognition has evolved independently in the magpie and great apes (which diverged 300 million years ago), and that the neocortex (which is not present in the bird's brains) is not a prerequisite for mirror self-recognition as previously believed. Here, we have replicated the experimental design used on magpies to determine whether jackdaws (Corvus monedula) are also capable of mirror self-recognition by passing the mark test. We found that our nine jackdaws showed a very high interest towards the mirror and exhibited self-contingent behavior as soon as mirrors were introduced. However, jackdaws were not able to pass the mark test: both sticker-directed actions and sticker removal were performed with a similar frequency in both the cardboard (control) and the mirror conditions. We conclude that our jackdaws' behaviour raises non-trivial questions about the methodology used in the avian mark test. Our study suggests that the use of self-adhesive stickers on sensitive throat feathers may open the way to artefactual results because birds might perceive the stickers tactilely.